Predictors of prolonged recovery following acceptance for disability benefits: a systematic review of observational studies. (19th October 2011) - Busse, Jason; Steenstra, Ivan; Riva, John; Ebrahim, Shanil; de Bruin, Linda; Guyatt, Gordon
Abstract : Objectives: A significant number of disability claims remain active for substantial timeframes and account for a disproportionally large amount of financial resources. We conducted a systematic review of studies that explored predictors of prolonged recovery following acceptance for disability benefits in order to better inform early identification of claims at risk. Methods: Eligible studies were observational studies that enrolled patients that were off work and in receipt of wage replacement benefits, and that explored variables associated with recovery. Teams of reviewers independently agreed on eligibility, assessed methodological quality, and extracted outcome data. All outcomes related to functional recovery were included and, when possible, we conducted meta-analyses. We planned, a priori, to perform stratified analyses according to whether studies evaluated functional outcome directly (eg, return to work) or by use of a surrogate, whether they did or did not meet various quality criteria, longer (1 year) versus shorter duration of follow-up, type of organisation proving benefits (government vs private), and shorter versus longer duration of the disabling complaint. Results: We identified 3876 potentially eligible studies, and retrieved 167 studies in full text; 66 proved eligible. The chance-adjusted between-reviewer agreement (phi) on full text eligibility was 0.76. We anticipate data from subsequent stages of the project will be available at the time of the Conference. Conclusions: Our findings should prove helpful for identifying disabled employees in receipt of benefits early in the claim process, which may facilitate more effective triaging of resources and improved outcomes.